Shifting perceptions in school choice: The impact of presenting high-quality schools first in recife's centralized admission system - Gregory Elacqua; Macarena Kutscher; Mateus Rodrigues; Danielle Nascimento (Inter-American Development Bank (IDB), 2024)
The potential efficacy of centralized school choice systems in reducing inequalities in access to high-quality schools may be hindered by informational frictions. In this paper, we experimentally evaluate a low-cost information intervention in the centralized school admission system (Matrícula Digital) of Recife, Brazil. The intervention modified how school vacancies were initially displayed on the application platform: the treatment group first saw schools listed by quality; the control group first saw them ordered by proximity to the student's home, i.e., the default order. We focus on students applying to first grade, the level with the highest participation rate since all pupils entering the municipal school system must go through this process. We find no overall effect of the school ordering change on the quality of the schools selected. However, when we restrict our analysis to students who live near at least one of the top three schools on the list, we observe a significant positive effect. This effect weakens as distance from home increases. Our findings indicate the importance of school quality in relation to proximity to the students residence. This conclusion is supported by a parental survey conducted after admissions, in which 80% of respondents indicated that proximity was the most important factor in their school choice. These results have considerable implications for the design of effective educational information interventions.
Keywords: A20; D12; I24; C93; H75; 330; school choice; centralized admission system; informationintervention; educational inequality